2020
DOI: 10.1007/s40257-020-00509-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes in BRAF-Mutated Melanoma Treated with Combined Targeted Therapy or Immune Checkpoint Blockade: Are We Approaching a True Cure?

Abstract: Approximately 50% of all melanomas harbor an activating BRAF mutation. In patients suffering from an advanced melanoma with such a somatic alteration, combined targeted therapy with a BRAF and MEK inhibitor can be applied to significantly increase the survival probability. Nevertheless, resistance mechanisms, as well as negative predictive biomarkers (elevated lactate dehydrogenase levels, high number of metastatic organ disease sites, brain metastasis), remain a major problem in treating melanoma patients. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 60 publications
0
38
0
4
Order By: Relevance
“…Approved combinations for patients with unresectable or metastatic melanoma include darafenib/trametinib, vemurafenib/cobimetinib and encorafenib/binimetinib [63]. Combination targeted therapy can also be beneficial in an adjuvant setting [64], and dabrefenib/trametinib has been approved for use as adjuvant treatment after complete resection of stage III melanoma [65]. However, in many patients, melanoma progression eventually occurs and resistance to treatment develops.…”
Section: Discussionmentioning
confidence: 99%
“…Approved combinations for patients with unresectable or metastatic melanoma include darafenib/trametinib, vemurafenib/cobimetinib and encorafenib/binimetinib [63]. Combination targeted therapy can also be beneficial in an adjuvant setting [64], and dabrefenib/trametinib has been approved for use as adjuvant treatment after complete resection of stage III melanoma [65]. However, in many patients, melanoma progression eventually occurs and resistance to treatment develops.…”
Section: Discussionmentioning
confidence: 99%
“…In choosing CBI over "conventional" treatments, the fundamental parameters for success of therapy such as mutational load, the presence of lymphocytes within the tumor and the expression levels of immune checkpoint molecules (e.g., PD-L1,) must always be taken into consideration [25][26][27]. Some limitation still have to be overcome in order to become the treatment of choice in the some malignancies, such as the costs of production, conservation, stability, and immunogenicity [28].…”
Section: Introductionmentioning
confidence: 99%
“…Somatic BRAF mutations are found in approximately 50% of cutaneous melanoma. Although both ICI and BRAF/MEK inhibitors have been shown to prolong survival in patients of BRAF ‐mutated melanoma, there remain no definitive recommendations of which therapy should be used as first‐line treatment for metastases or postoperative adjuvant therapy 5 . In our study, four out of 10 cases developed BM during BRAF/MEK inhibitor treatment, which was significantly higher than those treated with anti‐PD‐1 antibody monotherapy.…”
Section: Discussionmentioning
confidence: 61%
“…Recent clinical trials revealed that both immune checkpoint inhibitors (ICI) and BRAF/MEK inhibitors significantly prolonged the survival of melanoma patients when used for not only advanced stages but also postoperative adjuvant therapy 1–4 . ICI are used regardless of BRAF status, and durable responses are frequently observed despite a lower objective response rate (ORR) than BRAF/MEK inhibitors 5 . In contrast, BRAF/MEK inhibitors can be applied only for BRAF ‐mutated melanoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation